The Relationship of Reserve Account Disclosure Transparency and Accrual Earning Management with Audit Quality as Moderating - Latifah binti Nono; Siti Khomsatun (Jurnal Dinamika Akuntansi)
The purpose of this study is to examine the effect of transparency of reserve account disclosure on accrual earning management, and also to examine the role of audit quality as a moderator for the effect of transparency of reserve account disclosure on accrual earning management. The population in the study are companies listed on the Indonesia Stock Exchange with a sample period of 2012-2015. The sample selection technique used purposive sampling. The samples were obtained 350 observations of manufacturing companies listed in Indonesia Stock Exchange period 2012 to 2015. This study uses panel regression statistical method with unbalance panel data. The measurements used for Transparency of reserve account disclosure are word count, sentence count, and disclosure index. The results support the hypothesis which show that transparency of reserve account disclosure have negative significant effect on the accrual earning management, audit quality have negative significant effect on accrual earning management, and audit quality has a role as moderator (strengthen) the Negative effect between transparency of reserve account disclosure to accrual earning management.Nevertheless, the result is inconsistent in each model. This study concludes that accrual earning management can be minimized by selecting competent auditors and increasing transparency of accounts receivable accounts.